English for Specific Purposes: A Need Analysis on English Course in Islamic Banking Department - Ahmad Madkur (Bina Nusantara University, 2018)
This research was aimed at analyzing the type of English skills needed by the students of Islamic Banking (Perbankan Syariah) in IAIN Metro and figuring out the materials relevant to their needs. This was a qualitative study involving 25 students and 20 alumni who were working or had ever worked in the banks or BMTs. The data were obtained by employing interviews, questionnaires, documentation, and then analyzed by using Miles and Huberman model. The findings reveal that most of the students have less skill in English. However, the language skill that is needed at most by the students is speaking skill as the communicative skill and vocabulary as the language skill. It is also discovered that there are some problems, such as limited references, lack of supporting facilities, and learning duration that are encountered by both lecturers and the students. Then, referring to their needs, the materials do not yet accommodate the content focus in which the students can learn English related to banking issues. This research recommends that the syllabus should be revised and English should be taught in an integrative approach.